PENGARUH PENGGUNAAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR IPS PADA SISWA KELAS V SD GUGUS III KECAMATAN NANGGALO KOTA PADANG - utami, risa; muhammadi, muhammadi; fachrial, farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research was based on the low learning outcomes of the fifth grade students in social science caused by the lack of students’ interest in the learning process. The students assumed that social science is the difficult subject and it needs memorization. In addition, the learning methods used by the teachers were less varied and gave less opportunity for the students to actively participate during the learning process. As a result, the students tended to be passive and unmotivated during the process of learning. One of the methods that can be used to solve the problems is role playing method. Thus, this research was undertaken as an attempt to assess the effect of role playing method on the fifth grade students’ learning outcomes of social science. This study adopted a quasi-experimental research design with quantitative approach. The population of this research was all of the fifth grade students of SDN 05 and SDN 13 Gugus III Kecamatan Nanggalo Padang consisted of 62 students. The sample used in this research was probability sampling encompassed cluster random sampling or area random sampling. The instrument for data collection was the written test. The result of the research revealed that the average score of the experimental group (87.33) which applied the role playing method compared to the control class (86.83) showed better achievement. Therefore, this research showed that the use of role playing method has a more positive effect on fifth grade students’ learning outcomes in social science at SDN Gugus III Kecamatan Nanggalo Padang.   Keywords: Role Playing Method, Learning Outcomes